Student occupational choices their influencing factors and development implications - Barrido, Leticia P (Iloilo University of the Philippines in the Visayas, 1981)
This study aimed to find out the occupational choices of the National High school students in the Province of Iloilo. Specifically, it attempted to answer the following questions: 1. What are the occupations preferred most by the National High School senior students? 2. What are the alternative occupations of these students? 3. What factors affect the occupational choices of these students? 4. What are the implications of these occupational choices to the objectives of the Provincial Development Plan?
Special Problem (M.Ed.) -- Iloilo : University of the Philippines in the Visayas, April 1981.